Innovative Self-Confidence Webinar Intervention for Depression in the Workplace: A Focus Group Study and Systematic Development - Wan Mohd Azam Wan Mohd Yunus; Peter Musiat; June S. L. Brown (MDPI, 2022)
Brief face-to-face self-confidence workshops were effective in reducing depression among the public. Technological advances have enabled traditional face-to-face interventions to be adapted using unique technology-mediated platforms. This article details the formative development of a self-confidence web-based seminar (webinar) intervention for workplace depression. The first section discusses a qualitative study that explores the feasibility and acceptability of adapting the self-confidence workshops into a webinar platform on employees in the workplace. The second section describes the systematic development of this new webinar intervention informed by the qualitative study findings, a published systematic review, and previous face-to-face self-confidence workshops. The qualitative study involves three focus groups (n = 10) conducted in a small organization. Three themes were identified relevant to the running of the new self-confidence webinars in the workplace: personal (content, time and duration preference, features of the webinar, individual participation, personalization), interpersonal (stigma from others, engagement with participants/presenter, moderated interaction), and organizational (endorsement from management, work demand). For the intervention development, the format, structure, features, and content of the self-confidence webinar intervention are described. Features such as file sharing, virtual whiteboard, live chat, and poll are explained with the intervention primarily based on cognitive behavior therapy and coping flexibility concepts.